Male Hypogonadism and Disorders of Sex Development - Grinspon, Romina P.; Bergadá, Ignacio; Rey, Rodolfo A. (Frontiers in Endocrinology, 2020)
Disorders of Sex Development (DSD) are congenital anomalies in which there is a discordance between chromosomal, genetic, gonadal and/or internal/external genital sex. In XY individuals, the process of fetal sex differentiation can be disrupted at the stage of gonadal differentiation, resulting in gonadal dysgenesis, a form of early fetal-onset primary hypogonadism characterized by insufficient androgen and anti-Müllerian (AMH) hormone production, which leads to the development of ambiguous or female genitalia. The process of sex differentiation can also be disrupted at the stage of genital differentiation, due to isolated defects in androgen or AMH secretion, but not both. These are forms of fetal-onset hypogonadism with dissociated gonadal dysfunction. In this review, we present a perspective on impaired testicular endocrine function, i.e. fetal-onset male hypogonadism, resulting in incomplete virilization at birth.